Phenotypic Evaluation and Genetic Profiling of Shallot Genotypes Adapted to Peatland of South Kalimantan Using Simple Sequence Repeat (SSR) Markers - Reflinur, Reflinur; Handayani, Tri; M. Hidayat, Iteu; Sulastrini, Ineu; Salamiah, Salamiah; Pramudyani, Lelya; Waluyo, Nurmalita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The escalating demand of shallot has forced the increase of domestic production, including through extension of harvest area by utilization of arable land on peatland. This study was aimed to analyze genetic profile of shallot adapted in peatland areas using SSR markers. Twenty-one shallot genotypes were tested in the field and eighteen primers dispersed throughout the genome was applied to analyze genetic diversity of the peatland-adapted shallots. Phenotypic evaluation revealed that shallot yield potential ranged from 6.66 to 14.21 t/ha. Of these, seven shallot clones (11 NA, 1111 TA, 12 NA, 12 NC, 20 NA and 22 N) had good yield potential and comparable with those of five released shallot varieties. Nine out of 12 shallot clones were moderately resistant to Alternaria porii. Clustering analysis showed that shallot genotypes were clustered into two main groups, Clustered I and II which consisted of 13 and 8 genotypes, respectively. The closest genetic relatedness was observed between 8NC and 8NA (0.85), while the farthest ones was between 11NA and Kramat2 (0.51). This result implies that cross combination between 11NA and Kramat2 is valuable and suitable for breeding programs aimed at improving shallot potential yield in the future.